Perception-Driven Ballet Gesture Recognition and Evaluation System Using Kinect - Limmanee, Apirath; Buranasuk, Songphon (My University, 2021)
This paper shows the design and implementation of ballet gesture recognition and evaluation system with the Kinect camera. Similar research has been carried out in laboratory, but the real impact in dance community is still lacking. We therefore emphasize on the analysis regarding how different types of possible users perceive ballet dancing and let their perceptions shape our software design. This results in two computer programs designed for two specific user groups. The gesture recognition and evaluation used in both programs are customizable, sharing the same general framework proposed in this paper. Experimental steps for testing as well as improving the gesture recognition and evaluation are proposed together with preliminary result.
Keywords: ballet; education technology; gesture recognition; human computer interaction; MS Kinect